2020
DOI: 10.1021/acs.est.0c02040
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide as an Effective Soil Water Retention Agent Can Confer Drought Stress Tolerance to Paeonia ostii without Toxicity

Abstract: Graphene oxide (GO) is considered to be an emerging environmental pollutant with its inevitable release into the environment. Thus, its potential environmental risks and biosafety are receiving increased attention. In this study, Paeonia ostii was exposed to GO under drought stress. The results demonstrated that GO prevented soil water from evaporating due to its hydrophilic oxygen-containing functional groups and did not change the soil pH. Moreover, GO treatment resulted in lower increases in reactive oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…In addition, the previous studies showed that the surface morphology and internal structure of Paeonia ostii roots were not obviously different between GO and without GO treatment using SEM and TEM. Raman spectroscopy detection also indicated the absence of GO in the cells of the Paeonia ostii roots ( Zhao et al, 2020 ). He et al (2018a) also confirmed that GO could not accumulate in Spinacia oleracea L. seedlings cultivated in the soil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the previous studies showed that the surface morphology and internal structure of Paeonia ostii roots were not obviously different between GO and without GO treatment using SEM and TEM. Raman spectroscopy detection also indicated the absence of GO in the cells of the Paeonia ostii roots ( Zhao et al, 2020 ). He et al (2018a) also confirmed that GO could not accumulate in Spinacia oleracea L. seedlings cultivated in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Graphene oxide (GO), a novel nanomaterial as a soil water retention agent, plays a role in the growth and development of plants ( Shen et al, 2018 ; Xie et al, 2020 ). GO not only increased the drought tolerance of in Zea mays L. and Paeonia ostii ( Zhao et al, 2020 ; Lopes et al, 2021 ), but also enhanced the saline-alkali tolerance of Medicago sativa L. ( Chen et al, 2021 ). In addition, the previous studies showed that the surface morphology and internal structure of Paeonia ostii roots were not obviously different between GO and without GO treatment using SEM and TEM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomical observation referred to our previous studies [17,22]. Fresh leaves were cut into sections of 3 × 3 cm with a blade and then fixed in 2.5% glutaraldehyde solution at 4°C for at least 4 h. Then, the fixed leaves were washed three times with 0.1 mol/L phosphate buffer for 15 min each and were then sequentially dehydrated in a gradient of ethanol solutions (30%, 50%, 70%, 80%, 90%, 95%, and 100% solutions) for 15 min each.…”
Section: Observation Of Anatomymentioning
confidence: 99%
“…In our previous research, some drought stress-relevant indicators were measured, and we have tried to find useful ways to alleviate the drought stress of P. ostii [52,53]. At the same time, with the development of transcriptome sequencing, research on drought stress has gradually advanced and deepened from the physiological to the molecular level [54].…”
Section: Discussionmentioning
confidence: 99%